2006
DOI: 10.2175/193864706783791263
|View full text |Cite
|
Sign up to set email alerts
|

Odor Generation from Anaerobic Sludge: Role of Iron & Aluminum

Abstract: This study was conducted to determine the effect of iron and aluminum on odor generation from anaerobically digested and dewatered sludge cakes. Blended primary and waste activated sludge samples obtained from 12 different wastewater utilities was batch digested in the laboratory for 30 days at 37 o C, conditioned, dewatered and the organic sulfur odor generation potential measured. In addition to sulfur gas analysis, all sludge samples were analyzed for total and volatile solids, Fe and Al concentrations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…The results also appeared to show that the protein was degraded slower when iron was added. These results are in contrast to Verma et al (2006) , who reported that higher concentrations of iron in the feed to the digesters were correlated to greater peak total VOSC concentrations. Additional research is needed to fully investigate the potential of iron addition to reduce odorant production.…”
Section: Implications For Practicecontrasting
confidence: 99%
“…The results also appeared to show that the protein was degraded slower when iron was added. These results are in contrast to Verma et al (2006) , who reported that higher concentrations of iron in the feed to the digesters were correlated to greater peak total VOSC concentrations. Additional research is needed to fully investigate the potential of iron addition to reduce odorant production.…”
Section: Implications For Practicecontrasting
confidence: 99%
“…However, as indicated in the recent WERF III odor study (Adams et al 2007), addition of aluminium during centrifugal dewatering for sludge conditioning resulted in much lower odor generation from the dewatered sludge cakes. doi: 10.2166/wst.2010.300 The importance of this is that when iron or aluminium salts are added for phosphorus removal in the activated sludge system, they can also influence both the efficiency of anaerobic digestion and also the odors that are generated from the dewatered sludge (Verma et al 2006;Adams et al 2007). Therefore, this study was undertaken to better understand the effects of iron and aluminium salts added to activated sludge for phosphorus removal on anaerobic digestion and odor generation potential.…”
Section: Introductionmentioning
confidence: 99%